Resting state heart rate variability and false memories - Feeling, Nicole; Williams, DeWayne P.; Speller, Lassiter F.; Loftus, Elizabeth F.; Koenig, Julian; Thayer, Julian F. (International journal of psychophysiology, 2021)
Recent studies have shown higher resting-state vagally-mediated heart rate variability (vmHRV) to be related to greater memory retrieval. Research has not yet linked resting vmHRV with memory encoding and retrieval, as both are thought to play an important role in correctly distinguishing between true and false memories. The current study investigated this possible link in n = 71 undergraduate students. VmHRV was assessed during a 5-minute resting baseline period. Participants then completed the Deese-Roediger-McDermott (DRM) task, where they first viewed 6 word lists (12 words per list), and were later asked to identify previously shown words (true memories) and reject non-presented words. Results showed that participants with lower resting vmHRV were less able to discriminate true from false items. These data extend previous work on resting vmHRV and memory suggesting that resting vmHRV represents a psychophysiological pathway involved in both the proper encoding and retrieval of memories.
Gesehen am 18.10.2021